2013
DOI: 10.1007/82_2013_340
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Small GTPases by Legionella

Abstract: The pathogenic bacterium Legionella pneumophila interacts intimately with signaling molecules during the infection of eukaryotic host cells. Among a diverse set of regulatory molecules, host small GTPases appear to be prominent and significant targets. Small GTPases are molecular switches that regulate cellular signaling via their respective nucleotide-bound states: When bound to GDP, they are inactive, but become activated upon binding to GTP. Legionella secretes specific bacterial proteins into the cytosol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 64 publications
(116 reference statements)
0
27
0
Order By: Relevance
“…What is the purpose of Rab1A ubiquitination? Although monoubiquitination of Rab1 is novel, other forms of Rab1 modification have been described previously . In particular, the Legionella effectors DrrA and AnkX, respectively, AMPylate and phosphocholinate residues in the switch II region of Rab1.…”
Section: Resultsmentioning
confidence: 97%
“…What is the purpose of Rab1A ubiquitination? Although monoubiquitination of Rab1 is novel, other forms of Rab1 modification have been described previously . In particular, the Legionella effectors DrrA and AnkX, respectively, AMPylate and phosphocholinate residues in the switch II region of Rab1.…”
Section: Resultsmentioning
confidence: 97%
“…IQSEC2/ BRAG1 is mutated in X-linked nonsyndromic intellectual disability, a form of mental retardation (Shoubridge et al, 2010a;Shoubridge et al, 2010b). Arf proteins and their regulators are hijacked by numerous bacterial and viral pathogens (Dautry-Varsat et al, 2005;Goody and Itzen, 2013;Hsu et al, 2010;Humphreys et al, 2013;Matto et al, 2011). Legionella pneumophila and Rickettsia prowazekii encode an Arf GEF (RalF, acquired through horizontal transfer from their eukaryotic hosts), which recruits and activates Arf1 at the vacuoles that support its replication (Amor et al, 2005;Nagai et al, 2002).…”
Section: Arf Function In Mitosismentioning
confidence: 99%
“…The AnkX virulence factor is released into the macrophages by a type IV secretion system [24] and catalyzes the transfer of phosphocholine from CDP-choline to the Rab1 and Rab35 GTPases [25]. Since these GTPases are master regulators of vesicular trafficking, their inactivation results in the disruption of the host cell secretory pathway [26], presumably in a manner that favors establishment and maintenance of Legionella -containing vacuoles. Structural studies revealed that AnkX binds to its CDP-choline substrate in the opposite orientation of that for substrates binding canonical Fic proteins, similar to the manner in which Doc binds ATP [27].…”
Section: Phosphocholination By Ankxmentioning
confidence: 99%